APPLICATION OF RSA AND LSB IN SECURITY OF MESSAGES ON IMAGERY - Riza, Bob Subhan; Mashor, Mohd Yusoff; Haryanto, Edy Victor (ADI Journal on Recent Innovation (AJRI), 2019)
In this study is to discuss cryptography and steganography where the function is to insert a message or text into an image with JPG extension, the text to be inserted into the image has been encrypted using the RSA method so that the file is safer to be inserted into images, messages that are inserted into a blue image, this application aims to secure a message that you want to save, this application is made made using Android Studio and can be run on a mobile phone.